Influence of specimen shape deviations on uniaxial compressive strength of limestone and similar rocks. (December 2015) - Štambuk Cvitanović, N.; Nikolić, M.; Ibrahimbegović, A.
Abstract: The results of an experimental research program on ninety intact rock cylindrical test specimens are presented. The main goal is to examine the effect of specimen shape deviations (i.e. "micro" deviations from flatness, parallelism of ends and specimen axis perpendicularity) on uniaxial compressive strength ( UCS ) for limestone and similar rocks. The analysis of the results shows that in the case of the modern testing equipment there are no significant effects on the UCS value of neither parallelism nor axis perpendicularity for angle deviations up to 2°. The new proposed tolerance for flatness of specimen end (expressed as total height of the surface profile) is 0.08 mm, to be used with the aim of optimization and control over the aforementioned influences of test specimens in further compressive testing. The experimental research results related to the UCS were further re-examined by recently proposed numerical model based on Embedded Discontinuity Finite Element Method (ED-FEM) which proves a reliable interpretation of complex 3D failure mechanisms. We show an excellent correlation between the experiments and our numerical results, as a further confirmation of our findings. Highlights: Investigations include experimental tests on 90 specimens and 9 numerical tests. We examine effects of specimens shape deviations on UCS for limestone rock. The new specimens shape tolerances which are easier for use have been determined. The aim is optimization and control over influences of specimens shape in UCS tests. We show an excellent correlation between the experiments and numerical results.